Pengaruh Kompetensi, Disiplin Kerja, dan Budaya Organisasi Terhadap Kinerja Pegawai PT.Heat Exchanger Manufacturing Indonesia - irsad, cucunendro; hazizah, zalsa bella risky nur; fadillah, aprilia nur; handayani, rini (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the influence of competence, work discipline, and organizational culture on employee performance at PT. Heat Exchanger Manufacturing Indonesia. The research used a quantitative approach, collecting primary data through questionnaires from 30 employees. Data analysis was conducted using multiple linear regression. The results reveal that competence and organizational culture significantly affect employee performance, while work discipline has no significant effect. Competence contributes a 38.3% performance increase for each one-unit improvement, and organizational culture contributes 52%. Simultaneously, the three variables explain 95.7% of employee performance. This study concludes that competence and organizational culture are pivotal factors in enhancing employee performance, while work discipline requires support from other factors like motivation and work systems.